Metode Pembelajaran Sebagai Rekonstruksi Karakter Siswa - Moh Romli (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2019)
Making students who have the right, noble character and noble character, is the main goal of a teacher.Therefore, Ali Ahmad Madkur, an education expert and a Professor in the field of education curriculum developmentfrom Cairo University of Egypt, explained some of his thoughts related to the methods in Teaching and LearningActivities (at-thariqah at-ta'lim wa ta'alum). He put it in a very important part to make it easier for students to learn.Ali Ahmad Madkur, seeks to provide alternative solutions in teaching and learning methods to teachers (mu'alimun),which consist of various methods, such as habituation or exemplary, lectures, and interactions, discussions anddebates, stories, advice, penalties and rewards, etc. Ali Ahmad Madkur, has contributed ideas that can be used as abasis in teaching teachers so that they can be better understood by students, and trying with these methods, canreconstruct students' patterns of having noble character and character according to the expectations of parents, withfoundation ijmaliy (global) exposure in the guidance of the Holy Qur’an and the Hadith of the Prophet. Ali AhmadMazdkur strives in his thinking, advancing the world of Islamic education with the output of students or students whohave knowledge based on wisdom, character and noble character.